Strategic Balancing and Sovereign Autonomy: Indonesia’s Engagement with China in the Era of Regional Vulnerabilities - Tian, Tiecheng; Daud, Sity; Khairi, Aizat (Theoretical and Practical Research in Economic Fields; Vol 17 No 1 (2026): TPREF Volume XVII Issue 1(37) March 2026DO - 10.14505/tpref.v17.1(37).15, 2026)
This article discusses the continuing Chinese economic, strategic, and security interests in Indonesia, how investment in infrastructure, energy, and technology facilitates the modernization of Indonesia, as well as the alarming issues of debt sustainability, resource sovereignty, and regional power. Historical processes since Suharto to Jokowi show movement towards pragmatic cooperation and increasingly complex relationship with periods of contention and particularly in the case of the Natuna Islands where tensions are marked by the issues of competing sovereignty claims. The development of strategic autonomy also influences Indonesia to relate with China, although economic forces suggest the expansion of collaboration. The alliance with the United States and Japan and the active involvement in the ASEAN also reflects the intentions of Jakarta to preserve the balance in the situation in the region. The study analyses Sino-Indonesian relations through the prism of neorealist and national-interest perspectives with the help of which the interrelations between the two countries can be characterized by the existence of certain combination between cooperation and constraint created by the structural forces and national interests. Tightening governance and institutionalized protection is absolutely needed to guarantee that the Belt and Road Initiative undertakings are directed in the interest of the nation as well as policy independence. The results highlight the importance of the consistency of policymaking since Indonesia is to navigate the great-power rivalry, national politics, and public worries, due to the larger issue of development necessity versus the strategic foresight in the long run in Southeast Asia.